2020
DOI: 10.1186/s13075-020-02357-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body mass index on serum urate and renal uric acid handling responses to an oral inosine load: experimental intervention study in healthy volunteers

Abstract: Background High body mass index (BMI) is strongly associated with hyperuricaemia. It is unknown whether overweight and obesity influences serum urate primarily through increased urate production or reduced renal clearance of uric acid. The aim of this study was to determine the influence of BMI on the response to inosine, a purine nucleoside that functions as an intermediate in the purine salvage and degradation pathways. Methods Following an overnight fast, 100 healthy participants without gout attended a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Reinforced by Juraschek et al (2013), shows that in both survey periods, for the average American adult standing 1.76 meters (5 feet 9 inches), a BMI of 1 unit higher, corresponding to a greater 3.1 kg (~6.8 pounds) weight, was associated with a 5% greater prevalence of uric acid, even after adjusting for serum uric acid. Dalbeth et al (2020), also revealed that in a fasting state, people with high BMI experienced an increase in serum uric acid levels.…”
Section: Resultsmentioning
confidence: 90%
“…Reinforced by Juraschek et al (2013), shows that in both survey periods, for the average American adult standing 1.76 meters (5 feet 9 inches), a BMI of 1 unit higher, corresponding to a greater 3.1 kg (~6.8 pounds) weight, was associated with a 5% greater prevalence of uric acid, even after adjusting for serum uric acid. Dalbeth et al (2020), also revealed that in a fasting state, people with high BMI experienced an increase in serum uric acid levels.…”
Section: Resultsmentioning
confidence: 90%
“…BMI or weight can affect BMD as a result of the load factor [ 38 ]. According to Dalbeth et al, individuals with a high BMI exhibit reduced renal clearance after consuming dietary purines and have a larger renal capacity for UA reabsorption when fasting, with a higher BMI thus being associated with hyperuricemia [ 39 ]. It is thus possible that the positive relationship between UA and BMD is a consequence of obesity or higher BMI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increased urate reabsorption may be another cause of reduced urate excretion. Although pH did not affect transport of urate for URAT1 [ 51 ], it had been reported that URAT1 expression increased in renal tubules when insulin resistance, increasing the reabsorption of urate and then leading to the lower excretion of urinary urate and higher serum urate levels [ 52 ].…”
Section: Discussionmentioning
confidence: 99%